Stock Splits: Evidence from Mutual Funds - Rozeff, Michael S. (Journal of Finance, 1998)
Mutual fund splits occur in high-priced funds after unusually high returns. Split factors are related to the deviation of a fund's price from the mean of all fund prices. Post-split prices are below the mean of other funds' prices. Post-split numbers of shareholders and assets do not increase compared with funds having similar rates of asset growth. However, I find evidence that mutual fund splits bring per account shareholdings back up to normal levels. I argue that signaling, liquidity, and tick size theories do not apply to mutual fund splits.